Hy2Green: Remote laboratory of hydrogen technologies as an e-learning tool for training new professionals adapted to the new European energy model. Issue 2 (2020) - Vivas, F.J.; García, R.; Caparrós, J.J.; Segura, F.; Andújar, J.M.; Monforti, A.; Bocci, E.; Zotto, L. del; Arsalis, A.; Montero, E.; Rodríguez, M.; Leal, J.; et al.
Abstract: This paper presents a prominent e-learning tool that is part of deliverable packages of Hy2Green Project (Ref. 2017-1-ES01-KA203-038302). The aim of the project is to develop an online training course that can help to improve new professional profiles in hydrogen technologies, in line with the energy transition model in Europe. As part of this training course and as result of a team collaboration, a remote laboratory based on hydrogen technology has been designed and implemented. Through the online platform, students from every part of the world can access remotely and in real-time, to a real laboratory built from a scaled green-hydrogen production plant. The green-hydrogen production plant has, in addition to hydrogen production and storage subsystems, a fuel cell, through which electricity is generated with the stored hydrogen. The developed remote laboratory offers technological and educational improvements. From the technological point of view, it allows handling a real installation, throughout the entire energy conversion process, being able to carry out laboratory tests, to characterize the different components. This remote laboratory is proposed as a multidisciplinary tool, where students develop their skills in automatic control, system modelling and renewable energy management. On the other side, from the educational point of view, this proposal contributes to democratization of education. That is nowadays equipment related to hydrogen technology is not cheap, so this implies that not all educational centres cannot afford to have a hydrogen laboratory. The remote laboratory presented in this work offers the possibility to carry out laboratory practices to whatever the student and the university are.